Restoration of operational properties of aviation motor synthetic oil "Turbo-Nicoil" in the electric cleaner with polarizing filling - Гаража, В В.; авиденко, Ю. П. (Proceedings of National Aviation University, 2003)
It is considered process of clearing of oil in conditionally constant electric field. It is experimentally determined optimum modes and parameters of clearing of synthetic motor oil "Turbo-Nicoil" from mechanical pollution. There are resulted recommendations at the choice of a range of managing parameters for maintenance of the normalized values of criteria of cleanliness of oil